Experimental and theoretical study of Aspartic acid - Movre Šapić, Iva; Vidak, Andrej; Dananić, Vladimir (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2019)
The aim of this research is to detect zwittterionic structure of the aspartic acid and confirm the experimental spectra with quantum chemical calculations. The experimental IR and Raman spectra of aspartic acid powder show no vibrational bands of OH and NH stretching in expected spectral region. We assume that zwitterionic structure of aspartic acid is responsible for lowering the frequencies of these vibrations. An extensive experimental and computational research supports this assumption. Our DFT calculation strongly suggests the need for the dielectric environment in order to stabilize the zwitterionic structure of a single molecule. The network of intermolecular hydrogen bonding between aspartic acid molecules provides this dielectric environment. The DFT quantum mechanical calculations corroborate this assumption by optimizing a four-member group of molecules, which also gives an explanation of broad IR spectrum lines.